Changes in vascular density in the macula after pars plana vitrectomy for idiopathic macular hole with macular peeling and one type of flap - Tarková, Anna; Jirásková, Naďa; Dusová, Jaroslava; Marák, Jan; Studnička, Jan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
BACKGROUND AND AIMS: The aim of this study was to evaluate changes in vascular density in the macula after pars plana vitrectomy for idiopathic macular hole (IMD) with macular peeling and flap. METHODS: A prospective study of 35 eyes in 34 patients who had undergone standard surgery. Evaluated parameters were best-corrected visual acuity (BCVA), intraocular pressure (IOP), central macular thickness (CRT), macular volume (TMV) and vascular density of the superficial and deep capillary plexus. The follow-up period was one year. RESULTS: We divided the total group into two: temporal and circular flap and total group. We compared the values after surgery with the preoperative values. In the total group, BCVA increased from 48.38 to 71.44 letters (P≤0.05). IOP changed from 15.24 to 14.76 mmHg (P>0.05). CRT decreased from 432.27 to 323.64 μm (P≤0.05). TMV changed from 0.26 to 0.25 mm3 (P>0.05). The vascular density of the superficial plexus decreased from 32 to 28% (P≤0.05). The intercapillary space of the superficial plexus increased from 68 to 72% (P≤0.05). The vascular density of the deep plexus increased from 17 to 23%. The intercapillary space of the deep vascular plexus decreased from 83 to 77%. Changes in vascular density and intercapillary space of the deep plexus were statistically significant for certain months after operations (P≤0.05). There were no significant differences between subgroups. CONCLUSION: The superficial plexus vascular density is almost the same in the temporal flap and in the foveal-sparing flap is decreased, and the deep plexus vascular density increased statistically significantly during the follow-up period after surgery.
Keywords: Microvascular Density; Female; Tomography, Optical Coherence; ženské pohlaví; Intraocular Pressure; Retinal Vessels; chirurgické laloky; optická koherentní tomografie; Retinal Perforations; lidé; vitrektomie; Surgical Flaps; Vitrectomy; nitrooční tlak; macula lutea; prospektivní studie; Male; Prospective Studies; Aged; retinální cévy; lidé středního věku; senioři; mužské pohlaví; perforace sítnice; zraková ostrost; Visual Acuity; Middle Aged; mikrovaskulární denzita; Macula Lutea; Humans